Breastfeeding and the major fermentation metabolite lactate determine occurrence of Peptostreptococcaceae in infant feces - Huertas-Díaz, Lucía; Kyhnau, Rikke; Ingribelli, Eugenio; Neuzil-Bunesova, Vera; Li, Qing; Sasaki, Mari; Lauener, Roger P; Roduit, Caroline; Frei, Remo; Study Group, Ck-Care; Sundekilde, Ulrik; Schwab, Clarissa (Gut microbes, 2023)
Previous studies indicated an intrinsic relationship between infant diet, intestinal microbiota composition and fermentation activity with a strong focus on the role of breastfeeding on microbiota composition. Yet, microbially formed short-chain fatty acids acetate, propionate and butyrate and other fermentation metabolites such as lactate not only act as substrate for bacterial cross-feeding and as mediators in microbe-host interactions but also confer antimicrobial activity, which has received considerably less attention in the past research. It was the aim of this study to investigate the nutritional-microbial interactions that contribute to the development of infant gut microbiota with a focus on human milk oligosaccharide (HMO) fermentation. Infant fecal microbiota composition, fermentation metabolites and milk composition were analyzed from 69 mother-infant pairs of the Swiss birth cohort Childhood AlleRgy nutrition and Environment (CARE) at three time points depending on breastfeeding status defined at the age of 4 months, using quantitative microbiota profiling, HPLC-RI and 1H-NMR. We conducted in vitro fermentations in the presence of HMO fermentation metabolites and determined the antimicrobial activity of lactate and acetate against major Clostridiaceae and Peptostreptococcaceae representatives. Our data show that fucosyllactose represented 90% of the HMOs present in breast milk at 1- and 3-months post-partum with fecal accumulation of fucose, 1,2-propanediol and lactate indicating fermentation of HMOs that is likely driven by Bifidobacterium. Concurrently, there was a significantly lower absolute abundance of Peptostreptococcaceae in feces of exclusively breastfed infants at 3 months. In vitro, lactate inhibited strains of Peptostreptococcaceae. Taken together, this study not only identified breastfeeding dependent fecal microbiota and metabolite profiles but suggests that HMO-derived fermentation metabolites might exert an inhibitory effect against selected gut microbes.
Keywords: Exclusively breastfeeding; Gastrointestinal Microbiome; Oligosaccharides; kojení; Infant; fermentace; feces; Humans; kojenec; dítě; HMO fermentation metabolites; gut microbiota; Child; Lactic Acid; mateřské mléko; Female; Anti-Infective Agents; antiinfekční látky; lidé; acetáty; Feces; Fermentation; ženské pohlaví; Milk, Human; Clostridiales; Peptostreptococcaceae; oligosacharidy; střevní mikroflóra; Acetates; Breast Feeding; kyselina mléčná; lactate